Defining Teamwork Process and Skills for The Challenges Of The Future Workplace - Rafał KOZŁOWSKI; Beata MALIK - KOZŁOWSKA (Communications of International Proceedings, 2022)
By now it has been recognized that the formal higher education needs to change to meet the needs of future job requirements and the changing workplace dynamics. New technologies reshape the way we work, and it is crucial to equip students with skills that will let them adapt to new industries and move on to new career opportunities. In the case of business studies for years the pressure has been put on acquiring knowledge and functional and technical skills, while the development of soft skills has been neglected. Soft skills should be mastered by students to help them stay competitive in the fast-changing job market, as they can be easily transferred from one job to another. The purpose of this article is to define teamwork as one of the soft skills most frequently sought for by employers. To do that entrepreneurs and students were asked to provide their definitions of teamwork. Then literature was analyzed for the definition of teamwork.
Keywords: teamwork; skills set; workplace